3D kinematic and dynamic analysis of diagonal stride in elite backcountry skiing (SKIALP) - Pozzo, R.; Canclini, A.; Canclini, A. G.; Baroni, G. (Sciene and nordic skiing III, 2016)
In recent years the backcountry-skiing (SKIALP) has become more popular and SKIALP skiers have improved their technical and physiological performances. Due to the complex multiparametric environment conditions (air and snow temperature, track, techniques, gradients, boots, ski) and the relatively recent development of the discipline, there is a lack of specific studies especially under race conditions. On the other hand, technique and physiological analysis comparing normal race and treadmill conditions have been undertaken (Canclini 2007, Haselbacher 2014, Due 2011, Tosi 2009). The purpose of this study is to investigate the kinematics and in part the dynamics patterns of elite SKIALP skiers under normal competition conditions. Furthermore, a comparison with the technique used by elite cross country skiers is also presented.